KONTROL PEMERINTAH TERHADAP PEMBERANTASAN KORUPSI DI INDONESIA - Ihwanul Muttaqin (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2019)
Government control against corruption eradication in Indonesia is a form of overall supervision by the government of corruptors who want to undermine the country's finances, and can be as an effort to eradicate corruption in Indonesia to its roots. This study analyzes government control in the fight against corruption. This research is a normative legal research using a statutory approach and conceptual approach. The results showed that corruption should be classified as a crime whose eradication must be carried out extraordinarily. The function of government control in eradicating corruption is very much expected in the eradication of corruption in Indonesia, which is already rampant, namely the formation of the Corruption Eradication Commission (KPK).